4 Building on the best quality improvement programme – supporting improvements in end of life care in acute hospitals. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Hayes, A; Carey, I; Hill, R; Kennedy, M; Nash, K; Wakefield, D; James, M; Ison, L; Wood, D; Henry, C; Hayes, P
Abstract : Background: Building on the best (Botb), a 24 month partnership quality improvement (QI) programme delivered by Hospice UK aims to improve the quality of end of life care in acute hospitals. The programme design uses a collaborative methodology with flexibility for teams to work in alignment with local priorities. Methods: Four Improvement areas were prioritised for the collaborative by a clinical reference group:outpatient setting, communication of transfer, shared decision making, pain and symptom management. Teams received structured improvement coaching, monthly Webex, and the development of a community of practice.In addition to headline outcome and process measures, key outputs include teams' improvement case studies sharing impact and learning. Results: Botb currently encompasses 13 Trusts across England and Scotland. The collaborative has had 9 face to face community of practice learning events plus 18 monthly webinars. An example case study from Guy's and St Thomas' outlines testing on an acute admissions ward of a symptom observation chart and care planning guide for dying patients. A working group including the clinical lead and matron for acute medicine identified alignment of a local priority with Botb. Staff surveys and clinical audit demonstrated a positive impact on care planning and delivery. A positive feedback loop strengthened staff pride in the work of the ward. Success was boosted by a focus on influencing culture and delivery of flexible on the job education. These staff will now champion and support roll out within elderly care wards. The materials have been shared within the community of practice. Conclusions: Building on the best programme collaborative enables improvements by embedding systematic QI change methodology, supporting a mature community of practice to democratise knowledge and deliver results within complex systems by peer to peer learning.